PELATIHAN DAN PENDAMPINGAN DIGITAL MARKETING BAGI PELAKU UMKM DI DESA KERTOHARJO KELURAHAN KURIPAN KERTOHARJO - Ari Muhardono; Danang Satrio (LP2M STP Mataram, 2021)
Paguyuban Uripjoyo is an association of Micro Small Medium Enterprise (MSME) actors in Kuripan Kertoharjo Village. The impact of the pandemic outbreak and regulations related to the Imposition of Restrictions on Community Activities have caused sales turnover to decline, for that MSMEs are required to be more creative and innovative in carrying out marketing activities. Digital marketing activities or online marketing is the most appropriate solution in dealing with this phenomenon. However, there are still many MSME actors who have not mastered digital marketing. Therefore, digital marketing training and assistance is needed for MSME actors in Kertoharjo Village to be able to compete and be innovative to increase sales turnover in the pandemic era. This Digital Marketing Training and Assistance aims to provide knowledge and skills for MSME actors in Kertoharjo Village to increase sales through digital marketing